"Our fair trade coffee tastes better": It might, but under what conditions?. Issue 2 (9th November 2021) - Carr, Stuart C.; Meyer, Ines; Saxena, Mahima; Seubert, Christian; Hopfgartner, Lisa; Arora, Bimal; Jyoti, Divya; Rugimbana, Robert; Kempton, Heather; Marai, Leo
Abstract: The sustainability of Fair Trade ultimately relies on consumers choosing fair‐traded products. To date, research has tended to study consumer and producer engagement, and reactions to Fair Trade separately. These areas do, however, interconnect systematically through supply chains. In this paper, we introduce a self‐catalyzing model of Fair Trade which acknowledges those interconnections, traces them along supply chains from producer to consumer and addresses different international development priorities articulated in the United Nations Sustainable Development Goals. Its conceptual elements span (a) product quality, in this case, taste experience influenced by organoleptic properties and moral satisfaction; (b) organizational morality via corporate social responsibility and living wages; and (c) strategic management of slack farming resources—each catalyzed by, and catalyzing, positive emotions. Contingencies at each point in the model alter the likelihood that produce will be and feel fair and taste better to consumers.